Actualization of Religious Moderation Jurisprudence in Interacting with People of Other Religions - Agustiar (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2024)
This article outlines the conceptual implementation of the jurisprudence of moderation in the context of inter-religious interaction, with an emphasis on the foundation of the Quran. Through the analysis of Quranic verses that emphasize the values of tolerance, dialogue, and justice, this article highlights the importance of moderation as the primary principle in fostering harmonious relations between religious communities. The purpose of this research is to examine the concept of religious moderation in interactions with people of other religions from the perspective of the Quran. This research has implications for promoting better understanding between religious communities, building harmony, and preventing conflicts caused by religious incomprehension. This research is a library research that combines qualitative analysis of literature and text sources with an in-depth theoretical approach. In this context, the researcher will collect and analyze various relevant literature sources, such as books, journal articles, conference papers, and other academic documents related to this discussion. The findings of this research state: 1) The Qur'an consistently encourages Muslims to practice positive actions and reject negative behaviors. 2) Dialogue and good communication have a very important role in building positive relationships between religious communities. 3) The Qur'an explicitly rejects violence in the context of religion and invites its people to spread the message of peace.